ASPECTOS FLORÍSTICOS QUANTITATIVOS E COMPARATIVOS DA VEGETAÇÃO ARBÓREA DA RESERVA FLORESTAL DO SACAVÉM, SÃO LUÍS, MARANHÃO (BRASIL) - Muniz, Francisca Helena (1994)
An inventory was earried out in 0.5 ha of forest in lhe Sacavém Reserve of the Bacanga State Park. The Park is located in lhe São Luís city (2 32'S; 44 17'W). capital of the Stale of Maranhão, Brazil, al an altitude of about 30 m. The original vegetation consisted of a humid tropical forest locally termed 'Pre-Amazonian foiesl'. The sampling was made in remaining forest patches using 50 quadrais of 10x 10 m each. 410 trees were sampled with a minimum perimeter at breast height (PUH) of 15 cm, belonging to 34 families. 66 genera and I 10 species. A further 46 tree species distributed in 41 genera and 25 families were also included bui occunng outside the sampling area and were not used in the quanlitalive analysis. The OHI I varied between 4.8 cm and 86.7 cm. with a mean of 16.28 cm. The minimum, mean and maximum heights were 2.0 m. 11.6 in and 25.0 m. respctively. The results obtained here show that the Sacavém Reserve forest has a species richness index as high as oilier Amazonian locations and. although the mean values for height and diameter are low. its structure is also similar to the several studied sites of the same vegetation.